Monitoring of Surface Soil Quality Parameters of the Sitalakshya River, Bangladesh - Bhuyan, Md Simul; Rashed-Un-Nabi, Md; Hoque, Md Enamul; Sharif, Abu Sayeed Muhammad; Islam, Md Shafiqul (Review of Environment and Earth Sciences, 2018)
The present study was carried out to monitor and assess the surface soil quality parameters of the Sitalakshya River, Bangladesh. The soil samples were collected from Kanchpur Bridge and Atlapur during rainy and winter season. Soil texture is an important tool that aids in organic matter retention, minerals dispersal, microbial biomass, and other soil properties. The soil of the study area was recorded sandy loam and loam. The concentrations of soil parameters ranged for EC: 65.7 μS/cm-99.83 μS/cm; pH: 6.67-6.97; organic matter: 0.43%-0.66%; and organic carbon: 0.23%-0.35% in the soil of the Sitalakshya River. Most of the parameters showed no substantial variations in respect of sites and seasons (p>0.05) except electrical conductivity and pH (p<0.05). Statistical analysis like correlation matrix exposed the close relationship between organic matter and organic carbon. The soil of the Sitalakshya River has low nutrient contents that are not enough for the plants and organisms. Rapid industrialization and the huge establishment of brickfields are the major factors behind this less productive ecosystem. The river must be protected from further deterioration by taking fruitful management plan. This preliminary study will be a useful tool in the conservation plan. This will also help the future researchers who want to work on the river.